Novel NOMA MIMO designs for 5G and beyond - Saber Menaa (Universty Of El-oued جامعة الوادي, 2024)
The evolution of future generations of mobile wireless communication systems has intensified the demand for higher data rates, reduced latency, and improved spectral efficiency. Non-orthogonal multiple access (NOMA) has emerged as a groundbreaking solution to meet these demands. Which enables the sharing of time-frequency resources and utilizes successive interference cancellation (SIC) to mitigate interference among multiple users. As well, cooperative communications based on relays offer dependable connectivity and extend system coverage. While multiple inputs multiple outputs (MIMO) technology significantly contributes to the evolution of NOMA systems. The integration of MIMO using antenna selection (AS) schemes in NOMA enhances overall performance, decreases complexity and power consumption, which is a novel and appealing approach in this context. Within this thesis, we evaluate the effectiveness of implementing multi-antenna techniques within NOMA networks under realistic conditions, considering practical challenges such as SIC error, channel estimation error (CEE), and feedback delay error. The analysis begins with an examination of the single-input single-output (SISO) system in Downlink and Uplink NOMA networks, deriving mathematical expressions for ergodic capacity (EC), outage probability (OP), and bit error rate (BER). Subsequently, we investigate the MIMO-NOMA network, utilizing the joint transmit and receive antenna selection (JTRAS) protocol, and derive the expression for EC under realistic conditions. Later, we assess the performance of the Downlink cooperative NOMA network employing a relay selection strategy, incorporating both best relay selection (BRS) and partial relay selection (PRS) through the implementation of a transmit antenna selection (TAS) protocol. Finally, the thesis concludes with a comprehensive analysis of the results, highlighting challenges while offering valuable insights that can significantly influence future research in the field. أدى تطور األجيال القادمة من أنظمة االتصاالت الالسلكية المحمولة إلى تكثيف الطلب على معدالت بيانات أعلى، وخفض زمن الوصول، وتحسين كفاءة الطيف. وقد برز الوصول المتعدد غير المتعامد )NOMA )كحل رائد لتلبية هذه المطالب. مما يتيح مشاركة موارد الوقت والتردد ويستخدم إلغاء التداخل المتتالي )SIC )للتخفيف من التداخل بين المستخدمين المتعددين. كما توفر االتصاالت التعاونية القائمة على المرحالت ا موثوقا به وتوسع تغطية النظام. في حين تساهم تقنية المدخالت المتعددة والمخرجات المتعددة )MIMO )بشكل كبير في تطور أنظمة اتصاالا NOMA. يعمل دمج MIMO باستخدام مخططات اختيار الهوائي )AS )في NOMA على تعزيز األداء العام، وتقليل التعقيد واستهالك الطاقة، وهو نهج جديد وجذاب في هذا السياق. في إطار هذه األطروحة، نقوم بتقييم فعالية تنفيذ تقنيات الهوائيات المتعددة داخل شبكات NOMA في ظل ظروف واقعية، مع مراعاة التحديات العملية مثل خطأ SIC، وخطأ تقدير القناة )CEE)، وخطأ تأخير التغذية الراجعة. يبدأ التحليل بفحص نظام اإلدخال الفردي واإلخراج الفردي )SISO )في شبكات NOMA ذات االتجاه الهابط والصاعد، واستنباط التعبيرات الرياضية للسعة اإلرجودية )EC)، واحتمالية االنقطاع )OP)، ومعدل خطأ البت )BER). بعد ذلك، نقوم بالتحقيق في شبكة NOMA-MIMO، باستخدام ا، نقوم بتقييم أداء بروتوكول اختيار هوائي اإلرسال واالستقبال المشترك )JTRAS)، واستنباط التعبير عن EC في ظل ظروف واقعية. الحقا شبكة NOMA التعاونية ذات االتجاه الهابط باستخدام استراتيجية اختيار التتابع، ودمج كل من أفضل اختيار للتتابع )BRS )واختيار التتابع الجزئي )PRS )من خالل تنفيذ بروتوكول اختيار هوائي اإلرسال )TAS). أخي ارا، تختتم األطروحة بتحليل شامل للنتائج، مع تسليط الضوء على التحديات مع تقديم رؤى قيمة يمكن أن تؤثر بشكل كبير على األبحاث المستقبلية في هذا المجال.
في العلوم التكنولوجياTelecommunications Systems : أطروحة دكتوراه تخصص
Keywords: اختيار الهوائي(AS (، أفضل اختيار مرحل(BRS (، معدل خطأ البت(BER (، خطأ تقدير القناة(CEE (، السعة المريحة(EC (، اختيار هوائي اإلرسال واالستقبال المشترك(JTRAS (، مدخالت متعددة ومخرجات متعددة(MIMO (، وصول متعدد غير متعامد(NOMA (، احتمالية االنقطاع(OP (، اختيار مرحل جزئي(PRS (، مدخل واحد ومخرج واحد(SISO (، إلغاء التداخل المتتالي(SIC (، اختيار هوائي اإلرسال(TAS(.; antenna selection (AS); best relay selection (BRS); bit error rate (BER); channel estimation error (CEE); ergodic capacity (EC); joint transmit and receive antenna selection (JTRAS); multiple inputs multiple outputs (MIMO); non-orthogonal multiple access (NOMA); outage probability (OP); partial relay selection (PRS); single input single output (SISO); successive interference cancellation (SIC); transmit antenna selection (TAS).